2017
DOI: 10.1186/s40249-017-0243-0
|View full text |Cite
|
Sign up to set email alerts
|

A community-based survey of Toxoplasma gondii infection among pregnant women in rural areas of Taiz governorate, Yemen: the risk of waterborne transmission

Abstract: Background Toxoplasma gondii is a zoonotic coccidian parasite causing morbidity and mortality. In Yemen, T. gondii infection has been reported among pregnant women seeking healthcare in the main cities. However, no data are available on the prevalence of T. gondii infection and its associated risk factors among pregnant women in the rural communities of the country. Thus, the present study aimed to determine the seroprevalence of T. gondii and identify its risk factors among pregnant women in the rural communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
4

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 33 publications
5
17
4
Order By: Relevance
“…(43) The low IgM seropositivity rate (0.3%) in the present study is consistent with the low rate of 3.3% among pregnant women in rural areas of Taiz. (19) However, the low sensitivity of the tests used in the present study in the detection of anti-Toxoplasma IgM could not rule out the presence of false negativity. Therefore, it is difficult to compare the rate of anti-Toxoplasma IgM in the present study with studies adopting ELISA or other serological methods.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…(43) The low IgM seropositivity rate (0.3%) in the present study is consistent with the low rate of 3.3% among pregnant women in rural areas of Taiz. (19) However, the low sensitivity of the tests used in the present study in the detection of anti-Toxoplasma IgM could not rule out the presence of false negativity. Therefore, it is difficult to compare the rate of anti-Toxoplasma IgM in the present study with studies adopting ELISA or other serological methods.…”
Section: Discussioncontrasting
confidence: 55%
“…(18,23) In addition, it is lower than the rates reported among pregnant women residing in rural areas (46.2%) and those seeking antenatal care (44.0%) in Taiz. (19,20) On the other hand, it is comparable to that reported among pregnant women from the southern region of Saudi Arabia (20.0%), (24) but it is lower than the rates reported among pregnant women from Palestine (27.9%), (25) Egypt (30.2-67.5%), (26)(27)(28) Iraq (31.5%), (29) Sudan (34.1%), (30) Jordan (47.1%), (31) Tunisia (47.7-58.4%), (32,33) Algeria (47.8%), (34) Morocco (50.6%), (35) different regions of Saudi Arabia (29.4-61.4%), (36)(37)(38)(39)(40) Libya (44.8%), (41) and Kuwait (53.1%). (42) Variations in T. gondii seroprevalence could be attributed to climate conditions, differences in cultural and socioeconomic factors as well as hygienic and feeding habits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] The results were similar in every study conducted in Turkey. When we checked other countries, the seropositivity rates of T. gondii were 7% in Norway, 10% in the United Kingdom, 19% in Italy, 29.9 in Sri Lanka, [10] 31.7% in Thailand-Myanmar, [11] 32% in Spain, 33% in Austria, 34% in Slovenia, 44% in France, [12] 46.2% in Yemen, [13] and 82.6% in Lebanon. [14] Our results were similar to Mediterranean countries.…”
Section: Discussionmentioning
confidence: 99%
“…The author did not find any significant association between TLR4 rs4986790 or rs3050791 polymorphisms and toxoplasmosis. A previous study in Brazilian children with toxoplasmosis showed a relationship between the presence of C minor allele in TLR9 2848 G>A and the occurrence of ocular toxoplasmosis 11,12 .…”
Section: Discussionmentioning
confidence: 87%